Genetic Relationships in Malawian Cocoyam Measured by Morphological and DNA Markers. Issue 3 (1st May 2016) - Mwenye, Obed; Herselman, Liezel; Benesi, Ibrahim; Labuschagne, Maryke
Abstract : Cocoyam ( Colocasia esculenta L. and Xanthosoma sagittifolium L. Schott), a member of the Araceae family, has been cultivated for generations in Africa. Genotypes that adapt to local agroecological conditions and conform to social requirements have been selected by subsistence farmers. Knowledge of germplasm diversity and its genetic characterization is crucial to crop improvement and conservation strategies. Genetic relationships of cocoyam accessions collected from several districts across Malawi were analyzed using morphological, amplified fragment length polymorphism, and combined analyses. Two members of the Araceae family, Colocasia and Xanthosoma, were identified in the studied germplasm. Low levels of genetic variation were observed among accessions within each of the two species. There was consistency in the relationship of the cocoyam accessions using the different cluster and ordination methods as well as the analysis of molecular variance (AMOVA). The dendrograms, principal component analysis biplots, and AMOVA showed high levels of variation between the two species ( Colocasia and Xanthosoma ) and low levels among the different accessions within each of the two species. The genetic diversity of the accessions was also related to the different regions of collection and agroecology. Accessions from the southern region clustered separately from the ones collected from the northern region of Malawi.